THE INFLUENCE OF PSYCHOLOGICAL CAPITAL AND ORGANIZATIONAL CULTURE ON THE ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF HONORARY VOCATIONAL SCHOOL TEACHERS - Prayuda Nur Rifki; Laelatul Anisah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study aims to analyze the influence of psychological capital and organizational culture on the organizational citizenship behavior (OCB) of honorary teachers in private vocational schools in Kendal Regency. This study uses a quantitative approach with a survey design. The population in this study were all honorary teachers of private vocational schools in Kendal Regency, totaling 100 people from 17 private vocational schools. The sampling technique used was a non-probability census technique, so that the entire population was used as a research sample. The data collection method was carried out through the distribution of questionnaires. Data analysis used inferential statistics with the help of IBM SPSS 21, including validity tests, reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that the research instrument is valid and reliable and the data meets the classical assumptions. Hypothesis testing indicates that psychological capital and organizational culture simultaneously have a positive effect on the organizational citizenship behavior of honorary teachers. The results of partial and simultaneous tests indicate that both independent variables have a positive relationship with OCB. Thus, the research hypothesis is accepted. The conclusion of this study shows that increasing teachers' psychological capital and strengthening the school's organizational culture can encourage the emergence of organizational citizenship behavior, which is important for the effectiveness and sustainability of private vocational schools in Kendal Regency.